A model for facilities planning for multi-temperature joint distribution system - Hsu, Chaug-Ing; Liu, Kang-Po (Food control, 2011)
New technologies, such as replaceable cold accumulation and insulation box multi-temperature joint distribution (MTJD), provide precise temperature control, thereby reducing negative effects on food quality from exposure to extreme temperatures. This study compares conventional technologies with new ones, and constructs a binary integer-programming model to determine multi-temperature logistics techniques and food handling volume required for maximization of cost-efficiency in a hierarchical hub and spoke (H/S) network. It does so by minimizing the total delivery cost, comprised of terminal, food handling, and vehicle transportation costs computed, separately, by a derived algorithm. Appropriate technique(s) and handling volume for each terminal and vehicle routing are solved by Branch & Bound method, under the “best-first search” principle. The results indicate the model is feasible for facilities planning for MTJD. The replaceable cold accumulation and insulation box MTJD technique is suitable for operation networks with densely distributed terminals and uneven temporal and/or spatial demand distribution. ► We model facilities planning for multi-temperature joint distribution for food. ► We compare and incorporate the features of different techniques into the model. ► Optimal strategies are found for terminals and routing in hub and spoke operation. ► Old techniques are used if food volume is large. ► New technique with good temperature control is used for uneven and uncertain demand.